First words - Lloyd, Clare; Ward, Elle (London Dorling Kindersley, 2018)
Ideal for preschool play, First Words is full of bright pictures and common words from around the home such as teddy, dog, bird, sock, tree, flower, ball, and more. Read the simple rhyming text and lift the flaps to discover what - and who - is hiding underneath. Your little one will love recognising familiar objects on the page
1 2 23
Keywords: Vocabulary -- Juvenile literature; Vocabulary